The Export Debenture Plan for Aid to Agriculture - Davis, Joseph S. (Quarterly Journal of Economics, 1929)
Nature of the plan, 250. — I. The original Ketcham bill, 252. — The revised bill, 255. — II. An export bounty, little disguised, 255; but not a formal subsidy, 256. — III. Hamilton's proposals fundamentally different, 258; tho similar in some superficial respects, 261. — IV. Comparison with the German system, 263. — Some unexpected results of the changes made in 1906, 267. — German experience affords no support for the debenture plan, 268. — V. Not analogous to drawbacks, 269; or to protective tariffs, 271. — Hamilton's view, 273. — “Equality for agriculture,” 275. — VI. Conclusion: supporters of the debenture plan have relied on superficial analogies, 277.